Incidence and clinical outcomes of diabetes mellitus in HIV-infected adults in Thailand: A retrospective cohort study - Ninutcha Paengsai (2018)
© 2018 The Author(s). Background: Since 2005, Thailand has scaled up one of the largest antiretroviral treatment (ART) programs in South East Asia. Although diabetes mellitus (DM) incidence is increasing in low and middle-income countries, its burden and contributing factors in the HIV infected population are not well known. Methods: Using the Thai National AIDS Program data over a period of 8-years, we identified patients diagnosed with DM based on the following records: 1) fasting plasma glucose equal to or greater than 126 mg/dl following the 2013 American Diabetes Association criteria or 2) diagnosis codes E11-E14 of the 2010 WHO International Classification of Diseases, or 3) anti-diabetic drugs. Incidence was the number of new cases divided by that of person-years of follow-up (PYFU). Competing risks survival regression, treating death without DM as a competing event, was used to identify factors associated with DM. The risk of death in patients diagnosed with DM was estimated using Cox regression models. Results: Data of 763,666 PYFU from 199,707 patients (54.2% male; median age 36.2 years at registration with the program) were available and 8383 cases were diagnosed with DM, resulting in an incidence rate of 11.0 per 1000 PYFU. New DM diagnosis was more likely in men (adjusted sub-distribution hazard ratio 1.2), older patients (compared to patients 18 to 34 years old: 1.8 for 35 to 44; 3.0 for 45 to 59; 3.8 for ≥60), and if ART was initiated (1.3). In 2014, 1313 (16.6%) of 7905 diabetic patients had DM complications (11.5% microvascular complications and 6.9% macrovascular complications). Patients diagnosed with DM were at higher risk of death compared to the others. Conclusions: DM incidence was higher in this Thailand cohort of HIV infected adults than in the general population. Risk factors were similar to those in the general population, in addition to starting ART.